Perkembangan dan Pemanfaatan Teknologi Informasi Pengadilan Agama - Rifqi, Muhammad Jazil (Jurnal Al-Qadau: Peradilan dan Hukum Keluarga Islam, 2020)
AbstrakMelacak perkembangan Peradilan Agama tidak bisa terlepas dari histori di masa Kerajaan, masa Belanda, Masa Jepang dan era Kemerdekaan. Berangkat dari sejarah-sejarah tersebut, visi Mahkamah Agung dan lembaga pengadilan di bawahnya, termasuk Pengadilan Agama, untuk menjadi Peradilan Yang Agung bermula. Sebagai penyelesai sengketa bidang perdata agama, ternyata Pengadilan Agama juga mampu memanfaatkan teknologi informasi dalam mempermudah menyesaikan persoalan-persoalan baik dalam urusan internal organisasi maupun eksternal pencari keadilan. Perkembangan terakhir pemanfaatan teknologi telah diluncurkan e-Court dan e-Litigation dengan fungsi melakukan pendaftaran gugatan online (e-filling), panggilan elektronik (e-Summons), pembayaran elektronik (e-Payment), dan persidangan elektronik (e-Litigation). Hal ini tidak lain adalah implementasi asas trilogi Pengadilan yang dilakukan dengan sederhana, cepat dan biaya riangan.AbstractTracking the development of the Religious Courts cannot be separated from history in the Kingdom, the Dutch period, the Japanese Period and the Independence era. Departing from these histories, the vision of the Supreme Court and its lower court institutions, including the Religious Courts, to become the Supreme Court began. As a solution to religious disputes in the field of religion, it turns out that the Religious Courts are also able to utilize information technology in facilitating problems in both internal organizational matters and external justice seekers. Recent developments in the use of technology have been launched by e-Court and e-Litigation with the functions of registering online lawsuits (e-filling), electronic calls (e-Summons), electronic payments (e-Payment), and electronic trials (e-litigation). This is none other than the implementation of the Court trilogy principle, which is carried out simply, quickly and with cost.